Recruitment of CD16+ monocytes to endothelial cells in response to LPS-treatment and concomitant TNF release is regulated by CX3CR1 and interfered by soluble fractalkine. (July 2016) - Rennert, Knut; Heisig, Kerstin; Groeger, Marko; Wallert, Maria; Funke, Harald; Lorkowski, Stefan; Huber, Otmar; Mosig, Alexander S.
Highlights: CD16 + monocytes are efficiently recruited to endothelial cells (EC) in presence of LPS. TNF release is amplified upon CX3CR1-dependet CD16 + monocyte adhesion to EC. Fractalkine shed by CD16 + monocytes interferes with CD3CR1-dependent cell adhesion. Shedding of fractalkine thereby balances TNF release and CD16 + monocyte recruitment. Abstract: Fractalkine (FKN, CX3CL1) is a regulator of leukocyte recruitment and adhesion, and controls leukocyte migration on endothelial cells (ECs). We show that FKN triggers different effects in CD16 + and CD16 − monocytes, the two major subsets of human monocytes. In the presence of ECs a lipopolysaccharide (LPS)-stimulus led to a significant increase in tumor necrosis factor (TNF)-secretion by CD16 + monocytes, which depends on the interaction of CX3CR1 expressed on CD16 + monocytes with endothelial FKN. Soluble FKN that was efficiently shed from the surface of LPS-activated ECs in response to binding of CD16 + monocytes to ECs, diminished monocyte adhesion in down-regulating CX3CR1 expression on the surface of CD16 + monocytes resulting in decreased TNF-secretion. In this process the TNF-converting enzyme (TACE) acts as a central player regulating FKN-shedding and TNFα-release through CD16 + monocytes interacting with ECs. Thus, the release and local accumulation of sFKN represents a mechanism that limits the inflammatory potential of CD16 + monocytes by impairing their interaction with ECs during the initial phase of an immune response to LPS. This regulatory process represents a potential target for therapeutic approaches to modulate the inflammatory response to bacterial components.